1991
DOI: 10.1007/bf01252276
|View full text |Cite
|
Sign up to set email alerts
|

Linear arrays of homogenous mast cells in the dura mater of the rat

Abstract: Using fluorescence histochemistry, 5-HT, histamine and heparin were colocalized in a large population of cells in the dura mater thereby identifying them as mast cells. In addition, because these cells were highly sensitive to compound 48/80 and were densely packed with granules of a consistent density, they were identified specifically as 'connective tissue' mast cells. Other types of mast cells, i.e. 'mucosal' or 'neurolipomastocytes', were not present in the rat dura mater. 5-HT immunohistochemistry was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
2
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 72 publications
4
64
2
1
Order By: Relevance
“…In the supratentorial dura, rostral to the transverse sinus, mast cells were arranged in the distinctive "linear arrays" (Fig. 2) that have been described previously in this region of the dura (Dimlich et al, 1991). However, the region caudal to the transverse sinus exhibited an entirely different distribution, which included most prominently a dense accumulation in the area immediately caudal to the sinus and medial to the superior cerebellar veins, on either side of the midline (Fig.…”
Section: Mast Cell Stainingmentioning
confidence: 84%
See 2 more Smart Citations
“…In the supratentorial dura, rostral to the transverse sinus, mast cells were arranged in the distinctive "linear arrays" (Fig. 2) that have been described previously in this region of the dura (Dimlich et al, 1991). However, the region caudal to the transverse sinus exhibited an entirely different distribution, which included most prominently a dense accumulation in the area immediately caudal to the sinus and medial to the superior cerebellar veins, on either side of the midline (Fig.…”
Section: Mast Cell Stainingmentioning
confidence: 84%
“…The orientation of the two fibers systems illustrated with the DiI staining was described previously by Dimlich et al (1991). They observed that the connective tissue of the inner and outer dural layers were obliquely oriented relative to each other, and that the nerve fibers and mast cells within each layer were aligned with the connective tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the dura mater is the intracranial structure most heavily innervated by pain fibers, it is also populated by resident mast cells (MCs) in both humans (Artico and Cavallotti, 2001) and rodents (Dimlich et al, 1991;Rozniecki et al, 1999;. These granulated immunocompetent cells, which reside near blood vessels and in apposition to the meningeal nociceptive fibers (Rozniecki et al, 1999), have the capacity to initiate or amplify inflammatory responses by releasing a host of mediators such as histamine, serotonin, cytokines, and various lipid mediators, including leukotrienes (LTs) and prostaglandins (PGs) (Metcalfe et al, 1997;Mekori and Metcalfe, 2000).…”
mentioning
confidence: 99%
“…The morphology and immunophenotype of these cells were compatible with mast cells, which have been found to accompany dural arteries in considerable numbers. 28 In vivo treatment of rat dura with mast cell degranulator compound 48/80 causes loss of immunoreactivity for histamine in mast cells, indicating degranulation. The treatment also caused delayed and prolonged activation of meningeal afferents.…”
Section: Role For Cgrp Receptors In the Cranial Meningesmentioning
confidence: 99%